Pharmacokinetics of mirodenafil, a new erectogenic, and its metabolite, SK3541, in rats: involvement of CYP1A1/2, 2B1/2, 2D subfamily, and 3A1/2 for the metabolism of both mirodenafil and SK3541 - Young Hee Choi; Young Sun Lee; Myung Gull Lee; Tae Kon Kim; Bong-Yong Lee (Frontiers Media S.A., 2010)
Purpose. This study was performed to find which types of hepatic CYP isoforms are responsible for the metabolism of mirodenafil (a new erectogenic) and one of its metabolite, SK3541, using various hepatic CYP inducers and inhibitors in rats. Methods. Mirodenafil at a dose of 20 mg/kg was administered intravenously to control rats and rats pretreated with various CYP inducers and inhibitors. The disappearance of SK3541 was also measured in vitro hepatic microsomes of rats with and without CYP inducer and inhibitors. Results. Compared to controls, in rats pretreated with 3-methylcholanthrene, orphenadrine, and dexamethasone (main inducers of CYP1A1/2, 2B1/2, and 3A1/2, respectively), the non-renal clearances (CLNRs) of mirodenafil were significantly faster (by 39.4%, 59.3%, and 63.9%, respectively). However, compared to controls, in rats pretreated with quinine and troleandomycin (main inhibitors of CYP2D subfamily and 3A1/2, respectively), the CLNRs of mirodenafil were significantly slower (by 36.1% and 33.2%, respectively). In rat hepatic microsomes spiked with furafylline, quinine, and troleandomycin (main inhibitors of CYP1A2, 2D subfamily, and 3A1/2, respectively), the intrinsic clearances (CLints) for the disappearance of SK3541 were significantly slower (by 18.4%, 35.3%, and 51.5%, respectively) than controls. Also in rat hepatic microsomes pretreated with orphenadrine (a main inducer of CYP2B1/2), the CLint for the disappearance of SK3541 was significantly faster (by 55.5%) than controls. Conclusions. The above data suggest that hepatic CYP1A1/2, 2B1/2, 2D subfamily, and 3A1/2 are involved in the metabolism of both mirodenafil and SK3541 in rats.